Design and implementation of testbed using IoT and P2P technologies: improving reliability by a fuzzy-based approach. (2017) - Liu, Yi; Yamada, Masafumi; Oda, Tetsuya; Matsuo, Keita; Barolli, Leonard; Xhafa, Fatos
The internet of things (IoT) is a new type of internet application which enables the objects to be active participants with other members of the network. In P2P systems, each peer has to obtain information of other peers and propagate the information through neighbouring peers. However, in reality, each peer might be faulty or might send incorrect information. In our previous work, we implemented a P2P platform called JXTA-overlay, which provides a set of basic functionalities, primitives, intended to be as complete as possible to satisfy the needs of most JXTA-based applications. In this paper, we present the implementation of a testbed using IoT and P2P technologies. We also present two fuzzy-based systems (FPRS1 and FPRS2) to improve the reliability of the proposed approach. Comparing the complexity of FPRS1 and FPRS2, the FPRS2 is more complex than FPRS1. However, FPRS2 makes the platform more reliable.